2015
DOI: 10.1007/s11356-015-4949-x
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls and organochlorine pesticides in atmospheric particulate matter of Northern China: distribution, sources, and risk assessment

Abstract: The objectives of this work are to track the contamination levels, distribution characteristics, and sources of polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) in atmospheric particulate matter (APM) of Northern China and to provide more comprehensive and fundamental data for risk assessment of organochlorine contaminants (OCs) in environments. Samples were extracted and purified by the microwave-assisted extraction and solid-phase extraction system, respectively. PCBs and OCPs were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…The concentrations of sum of α-, β-, γ-, and δ-HCHs (ΣDDTs, ΣHCHs), and sum of endosulfan-I, endosulfan-II, and endosulfan sulfate (ΣSULPHs) found in the present study were compared with those found in other studies. Compared with the concentrations found in other parts of China, the concentrations of ΣDDTs in the present study were higher than those in Beijing metropolis (Cheng et al, 2011) and northern China (Ding et al, 2015) but lower than those in the Pearl River delta (Huang et al, 2014) and Tianjin (Wu et al, 2005). In addition, the concentrations of ΣDDTs in the Chengdu-Deyang-Mianyang economic region were much lower than those in the eastern Zealand coast of Denmark (1250 ng/g; Bräuner et al, 2011) and Romania (1130 ng/g; Dirtu et al, 2012); the concentrations were slightly lower than those observed in Canada (46 ng/g; Audy et al, 2018), the Czech Republic (42 ng/g; Audy et al, 2018), Pakistan (53 ng/ g; Ali et al, 2012), and Kopawa of Nepal (62.9 ng/g; Chandra Yadav et al, 2020); and the concentrations were higher than those reported in the United States in 2015 (8.4 ng/g; Arnold et al, 2018).…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…The concentrations of sum of α-, β-, γ-, and δ-HCHs (ΣDDTs, ΣHCHs), and sum of endosulfan-I, endosulfan-II, and endosulfan sulfate (ΣSULPHs) found in the present study were compared with those found in other studies. Compared with the concentrations found in other parts of China, the concentrations of ΣDDTs in the present study were higher than those in Beijing metropolis (Cheng et al, 2011) and northern China (Ding et al, 2015) but lower than those in the Pearl River delta (Huang et al, 2014) and Tianjin (Wu et al, 2005). In addition, the concentrations of ΣDDTs in the Chengdu-Deyang-Mianyang economic region were much lower than those in the eastern Zealand coast of Denmark (1250 ng/g; Bräuner et al, 2011) and Romania (1130 ng/g; Dirtu et al, 2012); the concentrations were slightly lower than those observed in Canada (46 ng/g; Audy et al, 2018), the Czech Republic (42 ng/g; Audy et al, 2018), Pakistan (53 ng/ g; Ali et al, 2012), and Kopawa of Nepal (62.9 ng/g; Chandra Yadav et al, 2020); and the concentrations were higher than those reported in the United States in 2015 (8.4 ng/g; Arnold et al, 2018).…”
Section: Resultscontrasting
confidence: 93%
“…The C Ave of ΣHCHs (2.85 ± 2.10 ng/g) was lower than the C Ave values found in Beijing (Cheng et al, 2011), Tianjin (Wu et al, 2005), and Armenia (Dvorská et al, 2012) but similar to those in northern China (Ding et al, 2015) and the Pearl River delta (Huang et al, 2014). The C Ave of ΣSULPHs (2.92 ± 2.36 ng/g) was lower than the C Ave values found in the Pearl River delta (Huang et al, 2014), northern China (Ding et al, 2015), and Armenia (Dvorská et al, 2012). The concentrations of HCHs and SULPHs were low in the atmospheric dustfall in the Chengdu–Deyang–Mianyang economic region.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, PCBs absorbed into particles gradually accumulate in the local atmosphere during the winter. For wind speed, previous studies suggested that higher wind speeds had a dilution effect on the local contaminant levels [15,17]. In contrast, positive correlations with wind speed were observed among PCB-105, 138, 187, and 170, as well as the indicator PCBs.…”
Section: Meteorological Conditionsmentioning
confidence: 77%